2014
DOI: 10.7448/ias.17.1.18844
|View full text |Cite
|
Sign up to set email alerts
|

Injecting drug use is associated with a more rapid CD4 cell decline among treatment naïve HIV‐positive patients in Indonesia

Abstract: BackgroundIt remains unclear whether the natural course of human immunodeficiency virus (HIV) differs in subjects infected through injecting drug use (IDU) and no data have been published from low- or middle-income countries. We addressed this question in an urban cohort in Indonesia, which is experiencing a rapidly growing HIV epidemic strongly driven by IDU.MethodsAll antiretroviral treatment (ART) naïve HIV-positive patients who had at least two subsequent CD4 cell counts available before starting ART were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 38 publications
0
26
0
3
Order By: Relevance
“…During more than 30 years of the HIV/AIDS epidemic, Brazil has maintained a concentrated epidemic, with an HIV prevalence rate less than 1% in the general population [39]. Despite earlier concerns about an increase in heterosexual cases and "feminization" of the epidemic, it seems the actual scenario is the predominance of HIV infection among MSM, similar to data from many other countries [49,50].…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…During more than 30 years of the HIV/AIDS epidemic, Brazil has maintained a concentrated epidemic, with an HIV prevalence rate less than 1% in the general population [39]. Despite earlier concerns about an increase in heterosexual cases and "feminization" of the epidemic, it seems the actual scenario is the predominance of HIV infection among MSM, similar to data from many other countries [49,50].…”
Section: Resultsmentioning
confidence: 54%
“…Although the assumption that the square root of CD4 count is linearly related to time since infection has frequently been used in different settings [12,14,15], other types of functions have also been proposed [38,39]. In addition, Rice and collaborators have suggested that besides age at diagnosis, ethnicity and region of birth are significant predictors of rate of CD4 decrease [15].…”
Section: Resultsmentioning
confidence: 99%
“…This finding is compatible with some similar studies and might be because of their impaired cellmediated immunity and more rapid CD4 count decline among these patients. 38,39 It is not conclusively defined which diagnostic test is better to evaluate LTBI in HIV-infected patients, and decisions about this subject is influenced by some factors such as cost, accessibility, and patient convenience. 39 Considering imposed cost caused by dissemination of disease in the community and treatment of the patients would convince us that QFT performance and even chemoprophylaxis of false positive ones would be more cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the stable or increased incidence of HIV in MSM in some communities where widespread use of ART has been established emphasises the concern that not enough is known about treatment as prevention for this crucial population. 28 There is interest in expanding ART to prevent HIV transmission, but in the group with the highest levels of ART use, men-who-have-sex-with-men (MSM), numbers of new infections diagnosed each year have not decreased as ART coverage has increased for reasons which remain unclear. ART has almost certainly exerted a limiting effect on incidence.…”
Section: Methods and Findingsmentioning
confidence: 99%